Bonedd y Saint: an edition and study of the genealogies of the Welsh saints - Lewis, Barry James (Dublin Institute for advanced studies, 2023)
"Medieval Wales was a land of saints. All over the country, churches, relics, images and wells kept the memory of holy men and women alive in the landscape. But the saints were also remembered in people’s view of the past, as the sons and daughters of kings, long-dead warriors of the heroic age and other figures of legend. This book presents an edition, translation and analysis of the main collection of saints’ genealogies, Bonedd y Saint. Each pedigree is individually edited, translated and provided with copious notes. Full attention is paid to the development of the pedigrees over time and the many additions that were made in the medieval and early modern periods. Two introductory essays survey the manuscript tradition and the text’s origin, history and cultural significance. This new edition will make Bonedd y Saint accessible to students of the cult of saints and the medieval church as well as early Welsh literature."--